2018
DOI: 10.1074/jbc.m117.812834
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic acid lowers cardiac mitochondrial enzyme activity by replacing linoleic acid in the phospholipidome

Abstract: Cardiac mitochondrial phospholipid acyl chains regulate respiratory enzymatic activity. In several diseases, the rodent cardiac phospholipidome is extensively rearranged; however, whether specific acyl chains impair respiratory enzyme function is unknown. One unique remodeling event in the myocardium of obese and diabetic rodents is an increase in docosahexaenoic acid (DHA) levels. Here, we first confirmed that cardiac DHA levels are elevated in diabetic humans relative to controls. We then used dietary supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 87 publications
4
36
0
Order By: Relevance
“…We found that peroxidized cardiolipin species were increased in db/db vehicle-treated mice while A30 treatment prevented this increase ( Figure 6, A and B, Supplemental Figure 10). These data suggest that renoprotection of ABCA1 inducers may be linked to modulation of DHA-rich cardiolipin species that have been previously reported to enhance oxidative stress and to be upregulated in diabetes (35)(36)(37), which may further reduce the oxidation of cardiolipin. Elamipretide treatment ameliorates podocyte loss and DKD.…”
Section: Resultsmentioning
confidence: 54%
“…We found that peroxidized cardiolipin species were increased in db/db vehicle-treated mice while A30 treatment prevented this increase ( Figure 6, A and B, Supplemental Figure 10). These data suggest that renoprotection of ABCA1 inducers may be linked to modulation of DHA-rich cardiolipin species that have been previously reported to enhance oxidative stress and to be upregulated in diabetes (35)(36)(37), which may further reduce the oxidation of cardiolipin. Elamipretide treatment ameliorates podocyte loss and DKD.…”
Section: Resultsmentioning
confidence: 54%
“…The specific activity of each complex was measured at 37°C using reagents and substrates specified previously. 48 For experiments involving C2C12 cells, Complexes I and V activities were measured in isolated mitochondria, whereas activities of other Complexes were measured in whole cells. Citrate synthase activity was measured on a 96-well plate using a commercially available kit (Sigma Aldrich, CS0720).…”
Section: Methodsmentioning
confidence: 99%
“…It is important to point out that in some cases of extreme CL remodeling, the acyl chains may be major drivers of changes in mitochondrial bioenergetics. We previously demonstrated that dietary docosahexaenoic acid promoted robust CL remodeling, which lowered cardiac respiratory enzyme activities through changes in protein-CL binding and formation of membrane microdomains (68).…”
Section: A Reduction In Tetralinoleoyl-cl Concentration But Not Substmentioning
confidence: 99%
“…For select experiments, the addition of cyt c (3.8 -17 M final concentration), as well as other proteins, to GUVs and GMVs occurred immediately prior to imaging. Samples were drawn into a rectangular capillary tube (VitroTubes) and mounted onto a glass microscope slide as previously shown (68,74).…”
Section: Construction Of Guvs and Gmvsmentioning
confidence: 99%
See 1 more Smart Citation